DENTAL CARE FOR PEOPLE WITH AUTISM SPECTRUM DISORDER - dos Santos Souza, Aldenízia; Jesus da Silva, Bruna; da Silva Miranda, Jaqueline; Luna de Souza, Lorenzo; de Souza Pereira, Malvina; Natágoras Alves de Albuquerque, Marcone; Aparecida de Araújo Lima, Maria; Neves do Nascimento, Mariano; Gomes de Sousa, Mauri; Éllen da Silva Lima, Vitória (Health and Society, 2023)
This paper addresses Autism Spectrum Disorder (ASD), a neurological condition that encompasses challenges in language, communication, and social interaction. The term “autism” originates from Greek and reflects the concept of internal absorption. The research highlights obstacles in dental care for individuals with ASD due to behavioral complexities, sensory sensitivities, and coexisting conditions such as anxiety. A study conducted by Castaño Novoa et al. suggests that a collaborative desensitization approach involving dentists and therapists can facilitate dental procedures in autistic adults, reducing the need for pharmacological interventions. Effective communication is essential, emphasizing mutual understanding and the use of the “tell-show-do” technique. The treatment of children with ASD faces challenges in communication, emotional regulation, and sensory sensitivity. Strategies of positive reinforcement and anxiety management are employed to encourage cooperation. The dental team must be prepared to deal with unconventional sensory responses, especially due to sensitive peripheral vision in autistic children. The research underscores the importance of understanding inappropriate behaviors post-desensitization and addresses the differentiation between inappropriate behaviors and stereotypes, emphasizing communication with parents, therapists, and doctors. Globally, the study highlights the significance of adaptation, effective communication, and understanding the intricacies of ASD in dental care, aiming to enhance the treatment experience and oral health of affected individuals.